Improving capacity and flow in a children and young people’s Community Eating Disorder Service (CEDS): how a quality improvement initiative led to a reduction in waiting times in the service - Sophia Ulhaq; Kamel Cheradi; Abab Ahmed; Kitty Thanki; Mark Dalby (BMJ Open Quality)
Eating disorders are serious mental health conditions associated with significant morbidity and mortality. High levels of demand on services have led to increases in wait times to access support. Early intervention of eating disorders is critical to prevent entrenchment of illness and improve prognosis, with long wait times associated with higher rates of relapse.The East London Community Eating Disorder Service has seen an increase in wait time for routine referral from the 2-week local target to 17 weeks. Additionally, there have been long wait times to access treatment, including therapy and psychiatry support.A quality improvement (QI) framework was used in June 2022 to tackle the issues with capacity and flow with an aim to reduce wait times for routine referral from 17 weeks to 2 weeks in 12 months.A QI project team was formed which sought to understand the demands and capacity of the system using process mapping.From this, the team created a driver diagram and used Plan, Do, Study, Act cycles to test change iteratively. Measurements and data were displayed on control and run charts to help learn from the change ideas tested.Improvements were made and sustained, including reduction of routine referral wait time from 17 weeks to 2 weeks in 12 months. Additionally, internal wait lists reduced from 73 patients on the psychiatry list to 0 in 3 months and from 50 families waiting for therapy to 0 in 7 months.A number of inactive cases reduced from 65 to 0 during testing, thus contributing to improved flow through the service. A striking £130 233.21 annual savings in agency staff expenditure was achieved by January 2023.This has enabled a positive culture shift in the service.